The Anti-Inflammatory Mediator, Vasoactive Intestinal Peptide, Modulates the Differentiation and Function of Th Subsets in Rheumatoid Arthritis - Raúl Villanueva-Romero; Irene Gutiérrez-Cañas; Mar Carrión; Selene Pérez-García; Iria V. Seoane; Carmen Martínez; Rosa P. Gomariz; Yasmina Juarranz (Journal of Immunology Research)
Genetic background, epigenetic modifications, and environmental factors trigger autoimmune response in rheumatoid arthritis (RA). Several pathogenic infections have been related to the onset of RA and may cause an inadequate immunological tolerance towards critical self-antigens leading to chronic joint inflammation and an imbalance between different T helper (Th) subsets. Vasoactive intestinal peptide (VIP) is a mediator that modulates all the stages comprised between the arrival of pathogens and Th cell differentiation in RA through its known anti-inflammatory and immunomodulatory actions. This “neuroimmunopeptide” modulates the pathogenic activity of diverse cell subpopulations involved in RA as lymphocytes, fibroblast-like synoviocytes (FLS), or macrophages. In addition, VIP decreases the expression of pattern recognition receptor (PRR) such as toll-like receptors (TLRs) in FLS from RA patients. These receptors act as sensors of pathogen-associated molecular pattern (PAMP) and damage-associated molecular pattern (DAMP) connecting the innate and adaptive immune system. Moreover, VIP modulates the imbalance between Th subsets in RA, decreasing pathogenic Th1 and Th17 subsets and favoring Th2 or Treg profile during the differentiation/polarization of naïve or memory Th cells. Finally, VIP regulates the plasticity between theses subsets. In this review, we provide an overview of VIP effects on the aforementioned features of RA pathology.